A Benchmark for 3D Reconstruction from Aerial Imagery in an Urban Environment - Smolic, Aljosa (My University, 2021)
This paper presents a novel benchmark to evaluate 3D reconstruction methods using aerial images in a large- scale urban scenario. In particular, it presents an evaluation of open-source state-of-the-art pipelines for image-based 3D reconstruction including, for the first time, an analysis per urban object category. Therefore, the standard evaluation presented in generalist image-based reconstruction benchmarks is extended and adapted to the city. Furthermore, our benchmark uses the densest annotated LiDAR point cloud available at city scale as ground truth and the imagery captured alongside. Additionally, an online evaluation server will be made available to the community.
VISAPP 2021 -16th International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications, 2021.
PUBLISHED
Keywords: Benchmark; 3D Reconstruction; Structure-from-Motion; Multi-View Stereo; Creative Technologies; Digital Engagement; Digital Humanities; Multimedia & Creativity; Other